Vegetable crops in farming systems for higher returns - Singh, Shrawan; Tomar, BS (Indian Horticulture, 2019)
Vegetable crops are short duration, high-yielding and remunerative. There are around 70 different vegetables cultivated commercially in diverse agroclimatic regions in India. These crops integrate well with different growing systems such as intercropping in perennial trees, cropping systems, integrated farming system, crop diversification and intensive cropping system. There is an increase in vegetable intake and prices also remain moderate to high except glut situation. Vegetable are getting popular in the farming systems to increase the farm income. New high-value vegetables, improved cultivars and agro-techniques in different vegetables favours their integration in farming system for higher income realization. Improved vegetable varieties/hybrids/ and developmental policies played key role in spatial and temporal expansion of vegetable production. High productivity value of fruits and vegetables (` 1,35,000/ha/annum) as compared to cereals (` 19,470), pulses (` 12,897) and oilseeds (` 26,098) attract growers.